2022
DOI: 10.36740/wlek202204121
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tae-Bo on the Development of Motor Potential of Students of Medical and Pedagogical Specialties and Its Efficiency in the Process of Extracurricular Activities

Abstract: The aim: The purpose of this article was to study the impact of Tae-Bo on the development of motor potential of students and its effectiveness in the process of extracurricular activities. Materials and methods: The experiment was conducted in the conditions of the educational process. An experimental group was formed, which was engaged in the traditional educational program of physical education and additionally three times a week, attended training in Tae-Bo. The control group was engaged in the traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Performance activities indicate artistic activities [ 14 ] and comprised five articles [ 2 , 3 , 37 , 47 , 75 ]. Team sports involve participation in one or more school sports teams [ 14 ] and included seven articles [ 2 , 34 , 36 , 52 , 61 , 72 , 74 ]. School involvement represents a self-governing body or entertaining club [ 14 ] and included four articles [ 3 , 23 , 31 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance activities indicate artistic activities [ 14 ] and comprised five articles [ 2 , 3 , 37 , 47 , 75 ]. Team sports involve participation in one or more school sports teams [ 14 ] and included seven articles [ 2 , 34 , 36 , 52 , 61 , 72 , 74 ]. School involvement represents a self-governing body or entertaining club [ 14 ] and included four articles [ 3 , 23 , 31 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…They found a workshop about stress [ 66 ] or leadership [ 31 ], and a mindfulness program [ 26 ] helped self-management. Five articles investigated the relation between EAs and physical health or physical ability [ 18 , 28 , 58 , 63 , 74 ], such as the prevalence of tuberculosis infection, vaccination coverage, and visual-spatial abilities. Two articles mentioned time use; participation in academic-scientific programs negatively predicted the use of social networks [ 56 ], and students reported that they lost time due to EA participation [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Performance activities indicate school band, drama, and/or dance [34] and comprised ve articles [2,3,37,44,45]. Team sports involve participation in one or more school teams [34] included seven articles [2,41,[46][47][48][49][50]. School involvement represents the student government, pep club, and/or cheerleading activities [34] and included four articles [3,41,51,52].…”
Section: Types Of Easmentioning
confidence: 99%
“…Three articles reported that EA participants could help students manage their time and stress [18,51,75]. Five articles investigated the relation between EAs and physical health or physical ability [20,47,63,67,68], such prevalence of tuberculosis infection, vaccination coverage, and visual-spatial abilities. Two articles mentioned time use; participation in academic-scienti c programs negatively predicted the use of social networks [53], and students reported that they lost time due to EA participation [52].…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…al., 2020;Emetc et. al., 2022;Shkola et. al., 2022), the modeling of professional training is used to: expansion of existing theories of organization of the educational process; regulation of the learning process of students, their personal and professional development, development and self-development; diagnostics of the state and dynamics of the formation of professional competencies, professional development, diagnostics of the quality of the educational process, determining the conditions for the formation of a competitive specialist in the modern labor market, etc.…”
Section: Introductionmentioning
confidence: 99%